Effects of lumacaftor—ivacaftor therapy on cystic fibrosis transmembrane conductance regulator function in F508del homozygous patients with cystic fibrosis aged 2–11 years - Berges, Julian; Graeber, Simon Y.; Hämmerling, Susanne; Yu, Yin; Krümpelmann, Arne; Stahl, Mirjam; Hirtz, Stephanie; Scheuermann, Heike; Mall, Marcus A.; Sommerburg, Olaf (Frontiers in Pharmacology, 2023)
Rationale: Lumacaftor/ivacaftor was approved for the treatment of patients with cystic fibrosis (CF) homozygous for F508del aged two years and older following positive results from phase 3 trials. However, the improvement in cystic fibrosis transmembrane conductance regulator (CFTR) function associated with lumacaftor/ivacaftor has only been studied in patients 12 years and older, while the rescue potential in younger children is unknown. Methods: In a prospective study, we aimed to evaluate the effect of lumacaftor/ivacaftor on CFTR biomarkers sweat chloride concentration (SCC) and intestinal current measurement (ICM) as well as clinical outcome parameters in F508del homozygous CF patients 2-11 years before and 8-16 weeks after treatment initiation. Results: A total of 13 children with CF homozygous for F508del aged 2-11 years were enrolled and 12 patients were analyzed. Lumacaftor/ivacaftor treatment reduced SCC by 26.8 mmol/l (p=0.0006) and showed a mean improvement in CFTR activity, as assessed by ICM in the rectal epithelium, to 30.5% of normal (p=0.0015), exceeding previous findings of 17.7% of normal in CF patients homozygous for F508del aged 12 years and older. Conclusions: Lumacaftor-ivacaftor partially restores F508del CFTR function in children with CF who are homozygous for F508del, aged 2-11 years, to a level of CFTR activity seen in patients with CFTR variants with residual function. These results are consistent with the partial short-term improvement in clinical parameters.